Model of dynamics of structured subpopulations of sturgeon fish in the Caspian Sea takes into account deviations in the rate of development of immature fish - Dubrovskaya, Victoria A.; Perevaryukha, Andrey Yu.; Trofimova, Inna V. (Experimental Biology and Biotechnology, 2018)
The article discusses modeling the dynamics of bioresources for the situation with a population that is divided into partially reproductively isolated groups of the initial population, which, when determining the exploitation strategy, is represented as a single commercial stock. In the case when fishing statistics are not able to delineate data on local groups that have ecological differences in reproduction, the role of secondary factors in assessing the efficiency of replenishment may increase, which is important for Caspian Sea sturgeons. Subpopulation groups unevenly retain the indicators expected from them by experts, according to forecasts of the success of reproduction with the same change in the hydrological situation. We propose to use as a supplementary indicator in the model of calculating the value of replenishment the development rate of juvenile, which may experience significant fluctuations due to intergroup competition. The system of differential equations is presented for analysis, where the developmental survival in the three ecology-physiological stages of juvenile development is significantly affected by the deviation in dimensional development, which is calculated from the basic phenomenological growth rate model given by the well-known von Bertalanffy equation. The dynamics for the trajectory obtained from the solution of the system of equations of a continuous-discrete iterative dynamic system is characterized by the possibility of attraction to two alternative cyclic attractors, which corresponds to fluctuating fluctuations with a high or low number for a complex-structured fish population.